ANALISA KELAYAKAN FINANSIAL PERANCANGAN PEMBANGKIT LISTRIK TENAGA BIOGAS (PLTBG) SEBAGAI SUMBER ENERGI BARU TERBARUKAN (STUDI KASUS: BALAI PIALAM YOGYAKARTA DPU-P ESDM DIY) - Agus Dwi Setiyono; Mathilda Sri Lestari, Ainur Komariah, Ig. Sudarno (PROSIDING, 2022)
Balai PIALAM Yogyakarta is an installation for processing household waste and human waste sludge located in Cepit Hamlet, Pendowoharjo, Sewon, Bantul, Yogyakarta. This study aims to determine the potential of biogas and electrical energy produced, as well as to analyze the financial feasibility of designing a biogas power plant (PLTBg) from the utilization of sewage sludge as a new renewable energy source (EBT). The object of this research is biogas which is produced from human waste sludge in a waste container (digester). The method used in this research is financial feasibility analysis. The result of this research is that the amount of fecal waste that enters the Balai PIALAM Yogyakarta is an average of 165 m/day and the capacity of the fecal receptacle is 497.28 m. The biogas produced is 16.6 m³/day with an electrical energy potential of 78 kWh/day. Utilization of biogas in fecal waste as raw material for biogas power plants (PLTBg) with an economic value of 15 years requires an investment of Rp. 75,203,500, - and the income is Rp. 13,374,278, -/year. The results of the financial feasibility analysis if the discount rate used is 9%, the NPV value is Rp. 29,662.124, -, the IRR is 15.32% greater than the discount rate used, the Net Benefit Cost Ratio is 1.39, and the Payback Period is 5 ,62 years. Keywords: Balai PIALAM, biogas, renewable energy source